Characterization of urea L-malic acid (ULMA) crystals grown in water, acetone and ethanol - P. Selvarajan2*, B. Sivasankari1 and (Journal of Experimental Sciences, 2010)
Urea L-malic acid (ULMA) salt was synthesized by dissolving urea and L-malic acid in the molar ratio 1:1 in de-ionized water heated at 45Â°C. The solubility of the synthesized salt was found in different solvents such as de-ionized water, ethanol and acetone in the temperature range 30-50Â°C.Â In accordance with the solubility data, saturated solutions for ULMA salt in different solvents were prepared and single crystals of ULMA were grown by solution method with slow evaporation technique at room temperature (30Â°C). It is noticed that the morphology of ULMA crystals is altered when they are grown in different solvents. The grown crystals were characterized by several studies such as X-ray diffraction (XRD) studies, solubility studies, UV-visible-NIR transmittance studies,Â microhardness studies.Â Second Harmonic Generation (SHG) studies revealÂ the Nonlinear(NLO) activity of the grown crystals. ——————————————————————————————————– <div style="border-right: medium none; padding-right: 0in; border-top: medium none; padding-left: 0in; padding-bottom: 1pt; border-left: medium none; padding-top: 0in; border-bottom: windowtext 1pt solid; mso-element: para-border-div; mso-border-bottom-alt: solid windowtext .5pt;"> 1Department of physics, Kalasalingam University, Krishnankoil-626 190, India; 2Department of Physics, Aditanar College of Arts and Science, Tiruchendur- 628216, Tamilnadu, India. * Corresponding Author, Email: pselvarajanphy@yahoo.co.in, Tel: +91 04639 243289; Fax: Â +91 04639 245247 Please Cite This Article As: B. Sivasankari and P. Selvarajan. 2010. Characterization ofÂ Â urea L-malic acid (ULMA) crystals grown in water, acetone and ethanol. J. Exp. Sci. 1(3): 1-3.<span style="font-size: 8pt; font-family: Symbol; mso-fareast-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: TA; mso-ascii-font-family: ’Times New Roman’; mso-hansi-font-family: ’Times New Roman’; mso-bidi-font-family: ’Times New Roman’; mso-char-type: symbol; mso-symbol-font-family: Symbol;">